Petroleum asphalt-based hard carbon material as well as preparation method and application thereof

By dissolving, drying, oxidizing and carbonizing petroleum asphalt powder, petroleum asphalt-based hard carbon materials with crosslinking structures and rich pore structures are prepared, which solves the problem of poor performance of hard carbon materials in the prior art and realizes the realization of the realization of High-performance battery material applications.

CN119284867APending Publication Date: 2025-01-10CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411220652.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The hard carbon materials obtained by direct preoxidation of petroleum asphalt have poor performance, which limits the further application of petroleum asphalt-based hard carbon materials.

Method used

By dissolving the petroleum asphalt powder in an organic solvent, filtration, drying and oxidizing, and then carbonizing at high temperature, a hard carbon material based on petroleum asphalt is prepared, a crosslinked structure and a rich pore structure are introduced to improve electrochemical performance.

Benefits of technology

This method improves the electrochemical performance of petroleum asphalt-based hard carbon materials, increases the carbon layer spacing, reduces ion embedding and disengagement resistance, improves the platform capacity and electrochemical performance of the battery, reduces manufacturing costs, and expands the application Scene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284867A_ABST
    Figure CN119284867A_ABST
Patent Text Reader

Abstract

The invention provides a petroleum asphalt-based hard carbon material as well as a preparation method and application thereof, and particularly relates to the technical field of secondary batteries. The preparation method of the petroleum asphalt-based hard carbon material comprises the following steps: A, dissolving petroleum asphalt powder in an organic solvent, and filtering after the petroleum asphalt powder is completely dissolved to obtain filter residues which are asphaltene; and B, drying asphaltene, oxidizing, and carbonizing the oxidized asphaltene at high temperature to obtain the petroleum asphalt-based hard carbon material. According to the preparation method, asphaltene is extracted firstly, a cross-linked structure is introduced after oxidation treatment, and in the subsequent high-temperature carbonization process, carbon layer rearrangement is inhibited, the distance between carbon layers is increased, and resistance in the ion embedding and removing process is reduced. Meanwhile, an oxygen-containing functional group introduced by oxidation is easily heated and decomposed into gases such as CO2 and H2O, so that a rich pore structure is brought to the material. The preparation method is simple in process flow, does not need complex equipment, provides a new treatment mode for the petroleum asphalt, and is beneficial to realizing high-value application of the petroleum asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a petroleum asphalt-based hard carbon material and a preparation method and application thereof. Background Art

[0002] Petroleum asphalt is an important petroleum product, and its sources are mainly two: one is from natural asphalt ore, and the other is from heavy oil processing such as vacuum residue, catalytic cracking oil slurry, steam cracking tar, etc. In general, petroleum asphalt is a black solid or semi-solid viscous substance with a very complex chemical composition. It is generally divided into saturated fractions, aromatic fractions, colloids and asphaltenes according to the group composition analysis method. Petroleum asphalt can be regarded as a colloidal system with asphaltene as the core, which absorbs part of the colloid to form micelles and is dispersed in the saturated fraction and aromatic fraction. Its molecular structure is mainly composed of C and H elements, and also contains S, N, O, Ni, V, etc.

[0003] For a long time, petroleum asphalt in my country has been mainly used in construction and road construction, with low industrial added value. In recent years, the production of high-performance carbon materials using petroleum asphalt as raw material has become a new research hotspot and economic growth point. The hard carbon materials obtained by direct pre-oxidation of petroleum asphalt in the existing technology often have unsatisfactory performance, which hinders the further application of petroleum asphalt-based hard carbon materials.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the objects of the present invention is to provide a method for preparing a petroleum pitch-based hard carbon material to solve at least one of the above-mentioned technical problems.

[0006] A second object of the present invention is to provide a petroleum asphalt-based hard carbon material.

[0007] A third object of the present invention is to provide an application of a petroleum asphalt-based hard carbon material.

[0008] In order to solve the above technical problems, the present invention particularly adopts the following technical solutions:

[0009] The first aspect of the present invention provides a method for preparing a petroleum pitch-based hard carbon material, comprising the following steps:

[0010] A. Dissolve petroleum asphalt powder in an organic solvent, filter after complete dissolution, and the resulting filter residue is asphaltene;

[0011] B. Drying the asphaltene and then oxidizing it to obtain oxidized asphaltene, and then carbonizing the oxidized asphaltene at high temperature to obtain a petroleum asphalt-based hard carbon material.

[0012] Furthermore, in step A, the organic solvent comprises a C5-C7 long-chain normal alkane.

[0013] Preferably, the C5-C7 long-chain normal alkane includes at least one of n-pentane, n-hexane and n-heptane, preferably n-heptane.

[0014] Furthermore, in step A, the particle size of the petroleum asphalt powder is 40 μm to 100 μm.

[0015] Furthermore, in step A, the mass ratio of the petroleum asphalt powder to the organic solvent is 1:10-40.

[0016] Furthermore, in step B, the drying temperature is 60° C. to 100° C., and the drying time is 6 h to 18 h.

[0017] Furthermore, in step B, the oxidation temperature is 200° C. to 400° C., and the time is 3 h to 20 h.

[0018] Furthermore, in step B, the high temperature carbonization temperature is 1000° C. to 1600° C., and the time is 2 h to 3 h.

[0019] The second aspect of the present invention provides a petroleum pitch-based hard carbon material prepared by the preparation method described in the first aspect.

[0020] The third aspect of the present invention provides the use of the petroleum pitch-based hard carbon material in the negative electrode of a secondary battery.

[0021] Furthermore, the secondary battery includes a lithium ion battery or a sodium ion battery.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] The preparation method provided by the present invention first pre-treats petroleum asphalt to extract asphaltene. Since asphaltene is more prone to coking, a cross-linked structure is introduced after oxidation treatment. In the subsequent high-temperature carbonization process, the rearrangement of the carbon layer is inhibited, the distance between the carbon layers is increased, and the resistance during the ion insertion and removal process is reduced. At the same time, the oxygen-containing functional groups introduced by oxidation are easily decomposed into CO by heat. 2 , H 2 O and other gases bring rich pore structures to the material, which is conducive to the improvement of platform capacity and greatly improves the electrochemical performance of the material. The preparation method has a simple process flow and does not require complex equipment. It provides a new way to treat petroleum asphalt, which is conducive to the realization of high-value applications of petroleum asphalt.

[0024] The petroleum asphalt-based hard carbon material provided by the present invention has a large carbon layer spacing and a rich pore structure. Using it as a negative electrode material is beneficial to improving the platform capacity and electrochemical performance of the battery.

[0025] The application of the petroleum asphalt-based hard carbon material in secondary batteries provided by the present invention provides secondary batteries with hard carbon materials with better performance, reduces the manufacturing and use costs of secondary batteries, expands the application scenarios of secondary batteries, and promotes the development of downstream industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 A flow chart of a method for preparing a petroleum pitch-based hard carbon material;

[0028] Figure 2 The NMR characterization diagram of the petroleum asphalt and asphaltenes of Example 1;

[0029] Figure 3 The XRD characterization diagram of petroleum asphalt and asphaltenes in Example 1;

[0030] Figure 4 FT-IR characterization diagram of petroleum asphalt and asphaltenes in Example 1;

[0031] Figure 5 This is the scanning electron microscope image of ZAOC-300-1200;

[0032] Figure 6 This is the scanning electron microscope image of ZAC-1200;

[0033] Figure 7 HRTEM spectrum of ZAOC-300-1200;

[0034] Figure 8 is the HRTEM spectrum of ZAC-1200;

[0035] Fig. 9 This is the element distribution characterization diagram of ZAOC-300-1200;

[0036] Fig.10 This is the XPS overall spectrum of ZAOC-300-1200 and ZAC-1200;

[0037] Fig.11 This is the C1s orbital XPS phase characterization diagram of ZAC-1200;

[0038] Fig.12This is the C1s orbital XPS phase characterization diagram of ZAOC-300-1200;

[0039] Fig.13 This is the O1s orbital XPS phase characterization diagram of ZAC-1200;

[0040] Fig.14 This is the O1s orbital XPS phase characterization diagram of ZAOC-300-1200;

[0041] Fig.15 XRD characterization diagram of ZAOC-300-1200 and ZAC-1200;

[0042] Fig.16 This is the Raman characterization spectrum of ZAOC-300-1200;

[0043] Fig.17 This is the Raman characterization spectrum of ZAC-1200;

[0044] Fig.18 This is the charge and discharge curve of the first three cycles of ZAOC-300-1200;

[0045] Fig.19 This is the charge and discharge curve of the first three cycles of ZAC-1200;

[0046] Fig. 20 This is the CV curve of ZAOC-300-1200 at a scan rate of 0.1mv / s;

[0047] Fig.21 This is the CV curve of ZAC-1200 at a scan rate of 0.1mv / s;

[0048] Fig. 22 The cycle performance diagram of ZAOC-300-1200 and ZAC-1200;

[0049] Fig.23 This is the rate performance diagram of ZAOC-300-1200 and ZAC-1200. DETAILED DESCRIPTION

[0050] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, but not all of the embodiments. The components of the embodiment of the present invention can be arranged and designed in various different configurations.

[0051] The first aspect of the present invention provides a method for preparing a petroleum pitch-based hard carbon material, comprising the following steps:

[0052] A. Dissolve petroleum asphalt powder in an organic solvent, filter after complete dissolution, and the resulting filter residue is asphaltene;

[0053] B. Drying the asphaltene and then oxidizing it to obtain oxidized asphaltene, and then carbonizing the oxidized asphaltene at high temperature to obtain a petroleum asphalt-based hard carbon material.

[0054] The preparation method provided by the present invention first pre-treats petroleum asphalt to extract asphaltene. Since asphaltene is more prone to coking, a cross-linked structure is introduced after oxidation treatment. In the subsequent high-temperature carbonization process, the rearrangement of the carbon layer is inhibited, the distance between the carbon layers is increased, and the resistance during the ion insertion and removal process is reduced. At the same time, the oxygen-containing functional groups introduced by oxidation are easily decomposed into CO by heat. 2 , H 2 O and other gases bring rich pore structures to the material, which is conducive to the improvement of platform capacity and greatly improves the electrochemical performance of the material. The preparation method has a simple process flow and does not require complex equipment. It provides a new way to treat petroleum asphalt, which is conducive to the realization of high-value applications of petroleum asphalt.

[0055] Figure 1 The present invention is a flow chart of the preparation method of petroleum asphalt-based hard carbon material. The petroleum asphalt is first crushed by ball milling to reduce the particle size of the petroleum asphalt and increase the specific surface area of ​​the material in contact with the organic solvent; the petroleum asphalt is dissolved in an organic solvent, and the saturated component, aromatic component and colloid are dissolved in the organic solvent, leaving the insoluble asphaltene, which is then oxidized and carbonized at high temperature to obtain the petroleum asphalt-based hard carbon material.

[0056] Through oxidation treatment, oxygen atoms are introduced into asphaltene, generating a large number of oxygen-containing functional groups, which decompose at high temperatures to produce small molecular gases, thereby introducing rich pore structures, enriching sodium or lithium storage sites, and increasing sodium or lithium storage capacity. At the same time, oxidation treatment can introduce cross-linking structures, transforming asphalt from thermoplastic to thermosetting, and preventing the melting and orderly rearrangement of asphalt during high-temperature carbonization.

[0057] Furthermore, in step A, the organic solvent comprises a C5-C7 long-chain normal alkane.

[0058] Preferably, the C5-C7 long-chain normal alkane includes at least one of n-pentane, n-hexane and n-heptane, preferably n-heptane.

[0059] Furthermore, in step A, the particle size of the petroleum asphalt powder is 40 μm to 100 μm.

[0060] When the particle size of petroleum asphalt powder is 40μm to 100μm, the petroleum asphalt powder has a large specific surface area and can fully contact with the organic solvent to remove the saturated components, aromatic components and colloids, leaving the asphaltene.

[0061] Furthermore, in step A, the mass ratio of the petroleum asphalt powder to the organic solvent is 1:10-40.

[0062] Typically but not limiting, the mass ratio of petroleum asphalt powder to organic solvent may be, for example, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35 or 1:40, or any value within the range of 1:10-40.

[0063] Furthermore, in step B, the drying temperature is 60° C. to 100° C., and the drying time is 6 h to 18 h.

[0064] The purpose of drying here is to remove the organic solvent in the asphaltene, and the drying temperature can be, for example, 60°C, 70°C, 80°C, 90°C or 100°C, and the drying time can be, for example, 6h, 8h, 10h, 12h, 14h, 16h or 18h.

[0065] Furthermore, in step B, the oxidation temperature is 200° C. to 400° C., and the time is 3 h to 20 h.

[0066] If the oxidation temperature is lower than 200°C and the time is lower than 3h, the oxygen functional groups cannot be effectively introduced into the asphaltene, thus affecting the oxidation effect. If the oxidation temperature is higher than 400°C, the asphaltene material will be severely coked, the introduced oxygen functional groups will be decomposed prematurely, and the asphaltene will be graphitized, affecting the sodium or lithium storage performance.

[0067] Typically but not limiting, the oxidation temperature can be, for example, 200°C, 250°C, 300°C, 350°C or 400°C, or any value in the range of 200°C to 400°C; the oxidation time can be, for example, 3h, 6h, 9h, 12h, 15h, 18h or 20h, or any value in the range of 3h to 20h.

[0068] Furthermore, in step B, the high temperature carbonization temperature is 1000° C. to 1600° C., and the time is 2 h to 3 h.

[0069] When the temperature of high-temperature carbonization is lower than 1000℃, it will cause incomplete carbonization, resulting in a reduction in pores and defects, which will reduce the sodium or lithium storage sites and reduce the sodium or lithium storage capacity in the platform area. When the temperature of high-temperature carbonization is higher than 1600℃, the oxidized asphaltene material will show a higher degree of graphitization, the degree of ordering of the carbon layer will increase, and the distance between the carbon layers will decrease, which is not conducive to the embedding and extraction of sodium or lithium ions, and will reduce the sodium or lithium storage capacity in the slope area.

[0070] Typically but not limiting, the temperature of high-temperature carbonization can be, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, or any value within the range of 1000°C to 1600°C; the time of high-temperature carbonization can be, for example, 12h, 18h, 24h or 30h, or any value within the range of 12h to 30h.

[0071] The second aspect of the present invention provides a petroleum pitch-based hard carbon material prepared by the preparation method described in the first aspect.

[0072] The petroleum asphalt-based hard carbon material provided by the present invention has a large carbon layer spacing and a rich pore structure. Using it as a negative electrode material is beneficial to improving the platform capacity and electrochemical performance of the battery.

[0073] The third aspect of the present invention provides the use of the petroleum pitch-based hard carbon material in the negative electrode of a secondary battery.

[0074] The application of the petroleum asphalt-based hard carbon material in secondary batteries provided by the present invention provides secondary batteries with hard carbon materials with better performance, reduces the manufacturing and use costs of secondary batteries, expands the application scenarios of secondary batteries, and promotes the development of downstream industries.

[0075] Furthermore, the secondary battery includes a lithium ion battery or a sodium ion battery.

[0076] In the following, some embodiments of the present invention are described in detail in combination with the embodiments and comparative examples. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0077] Example 1

[0078] This embodiment provides a petroleum asphalt-based hard carbon material, and the preparation method is as follows:

[0079] 1. Put petroleum asphalt in a ball mill and process it at 700 rpm for 4 hours to obtain powdered petroleum asphalt with a particle size of 50 μm to 60 μm.

[0080] 2. Dissolve the powdered petroleum asphalt in n-heptane solution. The mass of n-heptane is 20 times that of the petroleum asphalt. Stir well, filter out the insoluble asphaltene, and dry the asphaltene in a vacuum oven at 80°C for 8 hours.

[0081] 3. The asphaltene was placed in a tube furnace and oxidized at 300°C for 10 hours. After the oxidation treatment, the asphaltene was carbonized at a high temperature of 1200°C for 2 hours to obtain a petroleum asphalt-based hard carbon material, which was labeled as ZAOC-300-1200.

[0082] Example 2

[0083] This embodiment provides a petroleum asphalt-based hard carbon material, and the preparation method is as follows:

[0084] 1. Same as the step in Example 1.

[0085] 2. Dissolve the powdered petroleum asphalt in n-pentane solution. The mass of n-pentane is 40 times that of the petroleum asphalt. Stir thoroughly, filter out the insoluble asphaltene, and dry the asphaltene in a vacuum oven at 100°C for 6 hours.

[0086] 3. The asphaltene is placed in a tubular furnace and oxidized at 200°C for 20 hours. After the oxidation treatment, the asphaltene is subjected to high-temperature carbonization at a temperature of 1000°C for 3 hours to obtain a petroleum asphalt-based hard carbon material.

[0087] Example 3

[0088] This embodiment provides a petroleum asphalt-based hard carbon material, and the preparation method is as follows:

[0089] 1. Same as the step in Example 1.

[0090] 2. Dissolve the powdered petroleum asphalt in n-heptane solution. The mass of n-heptane is 10 times that of the petroleum asphalt. Stir well, filter out the insoluble asphaltene, and dry the asphaltene in a vacuum oven at 60°C for 18 hours.

[0091] 3. The asphaltene is placed in a tubular furnace and oxidized at 400°C for 3 hours. After the oxidation treatment, the asphaltene is subjected to high-temperature carbonization at a temperature of 1600°C for 2 hours to obtain a petroleum asphalt-based hard carbon material.

[0092] Example 4

[0093] This embodiment provides a petroleum asphalt-based hard carbon material. The difference from Example 1 is that the mass of n-heptane is 5 times the mass of petroleum asphalt. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0094] Example 5

[0095] This embodiment provides a petroleum asphalt-based hard carbon material. The difference from Example 1 is that the mass of n-heptane is 50 times the mass of petroleum asphalt. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0096] Example 6

[0097] This embodiment provides a petroleum asphalt-based hard carbon material. The difference from Example 1 is that the oxidation temperature in step 3 is 100° C. and the oxidation time is 2 hours. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0098] Example 7

[0099] This embodiment provides a petroleum asphalt-based hard carbon material. The difference from Example 1 is that the oxidation temperature in step 3 is 500° C. and the oxidation time is 10 h. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0100] Example 8

[0101] This embodiment provides a petroleum asphalt-based hard carbon material. The difference from Example 1 is that in step 3, the high-temperature carbonization temperature is 800°C and the time is 3 hours. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0102] Example 9

[0103] This embodiment provides a petroleum asphalt-based hard carbon material. The difference from Example 1 is that in step 3, the high-temperature carbonization temperature is 1800°C and the time is 2 hours. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0104] Example 10

[0105] This embodiment provides a petroleum asphalt-based hard carbon material. The difference from Example 1 is that step 1 is omitted and the petroleum asphalt raw material is directly dissolved in an n-heptane solution. The remaining raw materials and methods are the same as those in Example 1 and will not be repeated here.

[0106] Comparative Example 1

[0107] This comparative example provides a petroleum asphalt-based soft carbon material, and the preparation method is as follows:

[0108] 1. Same as the step in Example 1.

[0109] 2. Same as the step in Example 1.

[0110] 3. The asphaltene is placed in a tubular furnace for high-temperature carbonization at a temperature of 1200°C for 2 hours to obtain a petroleum asphalt-based soft carbon material, which is labeled as ZAC-1200.

[0111] Comparative Example 2

[0112] This comparative example provides a petroleum asphalt-based hard carbon material, and the preparation method is as follows:

[0113] 1. Same as the step in Example 1.

[0114] 2. Powdered petroleum asphalt is placed in a tubular furnace and oxidized at 300°C for 10 hours. After the oxidation treatment, the asphaltene is carbonized at a high temperature of 1200°C for 2 hours to obtain a petroleum asphalt-based hard carbon material.

[0115] Comparative Example 3

[0116] This comparative example provides a petroleum asphalt-based hard carbon material, and the preparation method is as follows:

[0117] 1. Same as the step in Example 1.

[0118] 2. Dissolve the powdered petroleum asphalt in n-heptane solution. The mass of n-heptane is 20 times that of the petroleum asphalt. Stir thoroughly and filter out the insoluble asphaltene.

[0119] 3. The asphaltene is placed in a tubular furnace and oxidized at 300°C for 10 hours. After the oxidation treatment, the asphaltene is subjected to high-temperature carbonization at a temperature of 1200°C for 15 hours to obtain a petroleum asphalt-based hard carbon material.

[0120] Characterization Example 1

[0121] The petroleum asphalt used in step 1 of Example 1 and the asphaltene dried in step 3 were characterized by NMR, and the images were as follows: Figure 2 shown.

[0122] By comparing the NMR characterization diagrams of original petroleum asphalt and asphaltene, it can be seen that after dissolution and filtration treatment, the impurities in the petroleum asphalt are successfully removed, the content of OC=O (ester / anhydride) increases, and the content of C=O and CO bonds decreases, making it easier for asphaltene to introduce cross-linking structures during the oxidation process.

[0123] Characterization Example 2

[0124] The petroleum asphalt used in step 1 of Example 1 and the asphaltene dried in step 3 were characterized by XRD, and the images were as follows: Figure 3 shown.

[0125] pass Figure 3 It can be seen from the XRD diffraction pattern that although the aliphatic carbon content of asphaltene is reduced, the γ peak of asphaltene is sharper, indicating that the distance between the aliphatic carbon chains of asphaltene is shorter, and oxygen can be directly incorporated into the carbon layer, which is more conducive to the introduction of cross-linked structure.

[0126] Characterization Example 3

[0127] The petroleum asphalt used in step 1 of Example 1 and the asphaltene dried in step 3 were characterized by FT-IR (Fourier infrared), and the images obtained were as follows: Figure 4 shown.

[0128] from Figure 4 It can be seen that the content of methyl and methylene in asphaltene is lower than that in petroleum asphalt, which is consistent with the results of NMR characterization, indicating that the other three components in asphalt are successfully removed.

[0129] Characterization Example 4

[0130] The hard carbon material ZAOC-300-1200 based on petroleum pitch obtained in Example 1 and the soft carbon material ZAC-1200 based on petroleum pitch obtained in Comparative Example 1 were subjected to scanning electron microscopy, and the obtained electron microscopy images correspond to the following: Figure 5 and Figure 6 shown.

[0131] from Figure 5 It can be seen that the petroleum pitch-based hard carbon material ZAOC-300-1200 presents an irregular block structure with a diameter between 10-20 μm, while the petroleum pitch-based soft carbon material ZAC-1200 presents a distinct flaky structure, indicating that the material has a high degree of graphitization.

[0132] Characterization Example 5

[0133] The petroleum pitch-based hard carbon material ZAOC-300-1200 obtained in Example 1 and the petroleum pitch-based soft carbon material ZAC-1200 obtained in Comparative Example 1 were respectively subjected to HRTEM imaging. The obtained HRTEM spectra correspond to the following: Figure 7 and Figure 8 shown.

[0134] from Figure 7 It can be seen that the petroleum asphalt-based hard carbon material ZAOC-300-1200 presents a short-range disordered state, has a large interlayer spacing, and forms some pore structures, which is conducive to the storage of sodium ions or lithium ions. Figure 8 It can be seen that the petroleum asphalt-based soft carbon material ZAC-1200 has a distinct carbon layer lattice, and its small interlayer spacing is not conducive to the embedding and extraction of ions.

[0135] Characterization Example 6

[0136] The element distribution characterization diagram of the petroleum pitch-based hard carbon material ZAOC-300-1200 obtained in Example 1 is shown in the following figure: Fig. 9 As shown. Fig. 9 It can be seen that the distribution diagrams are C and O, respectively. The element distribution diagram shows that oxygen is evenly distributed on the hard carbon surface, proving that the successful introduction of oxygen during the oxidation process has helped improve the material's sodium or lithium storage capacity.

[0137] Characterization Example 7

[0138] The petroleum pitch-based hard carbon material ZAOC-300-1200 obtained in Example 1 and the petroleum pitch-based soft carbon material ZAC-1200 obtained in Comparative Example 1 were characterized by XPS, and the obtained images were as follows: Fig.10 , Fig.11 , Fig.12 , Fig.13 and Fig.14 shown.

[0139] Fig.10 This is the XPS total spectrum of the two materials; Fig.11 This is the C1s orbital XPS phase characterization diagram of ZAC-1200; Fig.12 This is the C1s orbital XPS phase characterization diagram of ZAOC-300-1200; Fig.13 This is the O1s orbital XPS phase characterization diagram of ZAC-1200; Fig.14 This is the O1s orbital XPS phase characterization diagram of ZAOC-300-1200.

[0140] from Fig.10 , Fig.11 , Fig.12 , Fig.13 and Fig.14 It can be seen that there are four peaks corresponding to C=C, CC, CO, and C=O. The oxygen content of ZAOC-300-1200 material has changed, and the content of C=O bonds is obvious, providing more storage sites for ions. In addition, the higher content of COOH bonds provides more reversible adsorption sites for ions, which is conducive to the improvement of the first coulombic efficiency.

[0141] Characterization Example 8

[0142] The petroleum pitch-based hard carbon material ZAOC-300-1200 obtained in Example 1 and the petroleum pitch-based soft carbon material ZAC-1200 obtained in Comparative Example 1 were subjected to XRD phase characterization, and the obtained characterization diagrams are as follows: Fig.15 shown.

[0143] from Fig.15 It can be seen that the samples have obvious peaks at 25° and 43°, but the ZAOC-300-1200 material has an obvious hard carbon diffraction peak curve. According to the Bragg equation, the d(002) interlayer spacing values ​​of the ZAC-1200 material and the ZAOC-300-1200 material are calculated to be 0.354 and 0.373 nm, respectively. Generally speaking, when the interlayer spacing is greater than 0.37 nm, ions can be smoothly embedded and removed.

[0144] Characterization Example 9

[0145] The petroleum pitch-based hard carbon material ZAOC-300-1200 obtained in Example 1 and the petroleum pitch-based soft carbon material ZAC-1200 obtained in Comparative Example 1 were subjected to Raman characterization, and the obtained characterization spectra corresponded to the following: Fig.16 and Fig.17 shown.

[0146] from Fig.16 and Fig.17 By comparing the ID / IG in the graphite graphite matrix, it can be seen that the graphitization degree of ZAC-1200 is higher than that of ZAOC-300-1200, and the degree of disorder is reduced.

[0147] Test Case

[0148] The hard carbon material obtained in the embodiment and the comparative example was mixed with SuperP and PVDF binder in a ratio of 8:1:1 to form a slurry, which was coated on a copper foil current collector and dried in a vacuum oven at 80°C for 12 hours. The electrode sheets were cut into pieces and used as working electrodes.

[0149] Assemble half-cells for electrochemical testing. In a glove box under argon atmosphere, use sodium sheet as counter electrode and assemble the positive electrode shell, negative electrode shell, glass fiber separator, sodium sheet and electrolyte into a CR3032 button cell according to the correct operating steps. The electrolyte used is 1M NaClO 4 (EC / DEC=1:1). After the assembled battery was left to stand for 24 hours, constant current charge and discharge test and rate performance test were performed in the Xinwei test system, with the voltage range of 0.01-3.0V. The obtained data are shown in Table 1 below.

[0150] Table 1

[0151]

[0152]

[0153] Results

[0154] Plot the data in Table 1. Fig.18 This is the charge and discharge curve of the first three cycles of ZAOC-300-1200; Fig.19 This is the charge and discharge curve of the first three cycles of ZAC-1200; Fig. 20 This is the CV curve of ZAOC-300-1200 at a scan rate of 0.1mv / s; Fig.21 This is the CV curve of ZAC-1200 at a scan rate of 0.1mv / s; Fig. 22 The cycle performance diagram of ZAOC-300-1200 and ZAC-1200; Fig.23 This is the rate performance diagram of ZAOC-300-1200 and ZAC-1200.

[0155] from Fig.18 and Fig.19 It can be seen that ZAOC-300-1200 presents an obvious platform area, indicating that the introduction of oxygen functional groups effectively inhibits the ordering trend of asphaltene during the high-temperature carbonization process, allowing asphaltene to complete the transformation from thermoplastic material to thermosetting material, giving it more sodium storage sites. At the same time, its slope capacity is also improved compared to ZAC-1200 material.

[0156] Fig. 20 and Fig.21 CV curves with a scan rate of 0.1 m·Vs -1 , the scanning range is 0-3 V. The CV curve area of ​​ZAOC-300-1200 material is larger than that of ZAC-1200, indicating that ZAOC-300-1200 has a higher reversible specific capacity; the redox peak around 1.2 V corresponds to the formation of the electrolyte SEI layer, and the hard carbon material has a sharper redox peak around 0.1 V, indicating that the control of diffusion behavior contributes more to the capacity, which is in contrast to its higher platform capacity.

[0157] Fig. 22 Half-cells assembled from ZAC-1200 and ZAOC-300-1200 material samples at 30 mA g -1 Comparison of cycling performance under current density. ZAOC-300-1200 can output 305mAh·g after 100 cycles. -1 The reversible specific capacity of ZAC-1200 is only 105.3 mAh g -1 Reversible specific capacity.

[0158] Fig.23 The rate performance comparison curves of the two materials at different current densities are shown. The capacity of the hard carbon material is higher than that of the soft carbon material at all current densities. At the same time, when the current density is restored to 0.1C, the capacity of both hard carbon and soft carbon materials can be restored, showing good structural stability.

[0159] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a petroleum pitch-based hard carbon material, characterized in that: The following steps are involved: A. Dissolve petroleum asphalt powder in an organic solvent, filter after complete dissolution, and the resulting filter residue is asphaltene; B. Drying the asphaltene and then oxidizing it to obtain oxidized asphaltene, and then carbonizing the oxidized asphaltene at high temperature to obtain a petroleum asphalt-based hard carbon material.

2. The preparation method according to claim 1, characterized in that: In step A, the organic solvent comprises a C5-C7 long-chain normal alkane; Preferably, the C5-C7 long-chain normal alkane includes at least one of n-pentane, n-hexane and n-heptane, preferably n-heptane.

3. The preparation method according to claim 1, characterized in that: In step A, the particle size of the petroleum asphalt powder is 40 μm to 100 μm.

4. The preparation method according to claim 1, characterized in that: In step A, the mass ratio of the petroleum asphalt powder to the organic solvent is 1:10-40.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step B, the drying temperature is 60° C. to 100° C., and the drying time is 6 h to 18 h.

6. The preparation method according to any one of claims 1 to 4, characterized in that: In step B, the oxidation temperature is 200° C. to 400° C., and the oxidation time is 3 h to 20 h.

7. The preparation method according to any one of claims 1 to 4, characterized in that: In step B, the high temperature carbonization temperature is 1000° C. to 1600° C., and the time is 2 h to 3 h.

8. A petroleum pitch-based hard carbon material, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. Use of the petroleum pitch-based hard carbon material according to claim 8 in a negative electrode of a secondary battery.

10. The use according to claim 9, characterized in that: The secondary battery includes a lithium ion battery or a sodium ion battery.

Citation Information

Patent Citations

  • Porous hard carbon negative electrode material based on asphalt as well as preparation method and application of porous hard carbon negative electrode material

    CN115676804A

  • Oxidized asphalt-based hard carbon negative electrode material for sodium-ion battery and preparation method of oxidized asphalt-based hard carbon negative electrode material

    CN115991467A

  • Method for preparing asphalt-based hard carbon from heavy phase oil

    CN117049515A